Muslim Community Hampers Business On Non-Muslim Holiday Celebrations From the Perspective of Maqsid Syariah - Anja Santoso, Refons Cikafadupuri; Pagala, Azhar; Tanzilulloh, M. Ilham (Islamic Economic Law Study Program, Faculty of Sharia Sultan Aji Muhammad Idris Samarinda Islamic State University, 2024)
This study examines the differences of opinion between classical and contemporary scholars about whether or not it is permissible to provide needs or facilities for non-Muslim religious holidays. This is a promising business opportunity that can generate large profits. Muslim communities in Indonesia and in Samarinda City do a lot of hamper businesses on Muslim and non-Muslim holidays. In this case, there are three formulations of the problem in this study, namely, related to the background of Muslim communities doing hamper buying and selling businesses on non-Muslim holidays, then, the condition of the hamper business in Muslim communities during non-Muslim holidays, and also the Muslim community's hamper business on non-Muslim holidays from the perspective of maqashid sharia. This type of research is field research using normative legal and sociological legal approaches. The data sources used are secondary data sources and primary data. Data collection techniques are observation, interviews, documentation. Data analysis techniques in this study are data reduction, data presentation and drawing conclusions and inductive thinking patterns to draw conclusions. The results of this study indicate that the existence of hamper orders or the increasing number of consumer requests can help others, especially in non-Muslim holiday celebrations and sellers can take advantage to meet their needs, so this is the background for Muslim communities to do hamper business on non-Muslim holidays. The condition of the hamper business on non-Muslim holidays is very busy ordering and buying hampers. As for the maqashid sharia, it does not conflict with Islamic values ​​based on the rules of fiqh, namely